The Place of MS Sloane 3703 Among Early- Modern English Translations of the French Paraphrase of Splendor solis. (18th June 2019) - Bienias, Barbara
Abstract: This note identifies a hitherto anonymous astrological treatise—MS Sloane 3703 in the British Library—as one of the early-modern English translations of La Toyson d'Or (1612). The paper also investigates the correlation between MS Sloane 3703 and other known early-modern English versions of this text, found both in the Sloane collection and the Ashmole collection of the Bodleian Library in Oxford. The note is focused on the figure of William Backhouse (1593–1662), Elias Ashmole's 'spiritual father', in the context of his potential authorship of the translation done in Sloane 3703. The emphasis is put on the similarities and differences between the known translations of La Toyson d'Or and Sloane 3703, shedding some new light on the connections between the Sloane and Ashmole collections, something worthy of further attention.